A Fiber Laser Using Graphene-Integrated 3-D Microfiber Coil - Cheng Li; Jin-hui Chen; Shao-cheng Yan; Fei Xu; Yan-qing Lu (IEEE Photonics Journal)
We demonstrate a state variable fiber pulse laser based on a graphene-integrated microfiber device. A 3-D microfiber coil integrated with graphene acts as a polarization-sensitive saturable absorber. By adjusting the polarization controllers, stable Q-switched pulses and mode-locked rectangular pulses are observed. To our knowledge, this is the first study conducted to achieve switching between rectangular pulses and Q-switched pulses while keeping the pump power constant. The rectangular pulses have a pulsewidth and repetition rate of ∼10 ns and ∼940 kHz, respectively, and the Q-switched pulses have a pulsewidth and repetition rate of ∼40 $μs$ and ∼4.8 kHz, respectively.